Developmental origins of health and disease - Gluckman, Peter D.; Hanson, Mark A. (Cambridge University Press, 2006)
This landmark publication provides the first definitive account of how and why subtle influences on the fetus and during early life can have such profound consequences for adult health and diseases. Although the epidemiological evidence for this link has long proved compelling, it is only much more recently that the scientific and physiological basis for this has begun to be studied in depth and fully understood. This compilation, written by many of the world's leading experts in this exciting field, summarizes these scientific and clinical advances. The link between early development and the onset of many chronic diseases such as coronary heart disease, diabetes and osteoporosis, also raises important public health issues. Another fascinating theme in the book concerns evolutionary developmental biology and how the 'evo-devo' debate can cast light on these concepts. Clinicians and scientists alike will all learn a lot about this exciting and emerging field.